Synthesis of flourescent carbon nanoparticles from Chlorella sorokiniana for the detection of ferrous ions. - Crisostomo, Ryan Rey S. (2024.)
Iron has the potential to induce direct harm to the mucous membrane of the gastrointestinal tract, as well as vasodilation and hindered cellular metabolism in vital organs such as the heart, liver, and central nervous system. Excessive iron in water can lead to hemochromatosis, a condition characterized by the accumulation of excess iron in the bodies of animals, not just humans. Several efforts have been made in recent years to create efficient, sensitive, and selective sensors for the detection of iron ions. In response, microalgae-based fluorescent carbon nanoparticles (M-FCNs) were successfully synthesized from Chlorella sorokiniana through the hydrothermal method for the detection of Fe (II) ions. The parametric study using two-level (2k) full factorial for the synthesis of the M-FCNs determined that reaction time, reaction temperature, and their interaction were significant parameters, and both factors were directly proportional to the fluorescence intensity of the synthesized M-FCNs. The average particle size of the M-FCNs was 110 nm. Optical properties of the M-FCNs showed an absorption peak at 263 nm and exhibited a maximum fluorescence intensity of 70,205 a. u. at an emission wavelength of 450 nm within the green-light region when excited at 390 nm. The synthesized M-FCNs were used for the detection of Fe (II) ions. The M-FCNs exhibited captivating sensitivity toward Fe (II) with a linear range from 0.5 to 50 mg L-1 and a detection limit (LOD) of 0.70 mg L-1 (0.12 μM). In this study, the LOD was lower than the allowable iron level set by the Philippine National Standards for Drinking Water which is 1 mg L-1, indicating that the synthesized M-FCNs are a good sensing probe for detecting trace amounts of Fe (II) ions.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2024.
Keywords: Flourescent Carbon nanoparticles; Ferrous ions